Crecimiento de frutos y ramas de manzano ‘anna’ (malus domestica (2003)
Growth curves of fruits and shoots in relation to time afterfull bloom of “Anna” apple trees growth at 2470 m altitudewere determined in Paipa (Colombia). The evaluatedparameters in fruits every four days were: fresh weight,dry weight, length /diameter ratio of fruits. Shoot growthwas meassured at the same periodicity that by fruits. Theregression ecuations for evaluated parameters are reportedin this paper. The fresh weight increase of fruits wasslow until 46 days after full bloom (dafb), then it wasquickly until 62 dafb; among 62 and 74 dafb appeared aslow growth phase again; and finally, the growth intensityincreased until the ripening time. The dry weight increaseof fruits was slow until 58 dafb; and then it was quicklyuntil 94 dafb und finally decresased from 94 dafb. Thelength /diameter ratio decreased until 90 dafb and then itstabilished. Shoots grew quickly until 70 dafb, and thentheir growth intensity decreased among 70 and 94 dafb;and finally, their growth delayed from 94 dafb. With thisinformation it is possible to make a more rationale plan forsome culture activities at this apple variety cultured in theColombian highlands, that present similar agroecologicalconditions to those in which this study was done.